Effects on logistic operations from RFID- and EPCIS-enabled traceability - Ringsberg, Henrik Anders; Mirzabeiki, Vahid (Emerald Group Publishing Limited, 2014)
Purpose – The paper aims to explore the potential effects on logistic operations of implementing the Electronic Product Code Information Service (EPCIS) standard and radio frequency identification (RFID) technology to enable food traceability. A conceptual model for analysing supply chains according to EPCIS standard is also presented.Design/methodology/approach – A literature review was conducted to establish a theoretical framework. A case study of a Swedish fresh fish supply chain was then carried out.Findings – Implementation of the EPCIS standard and RFID technology to enable food traceability potentially affects the following logistic operations activities: identification, monitoring, labelling, goods handling, reporting of production, identification costs and revenue changes due to sales of goods. The conceptual model was used to analyse the effects.Research limitations/implications – The paper contributes to logistic research by studying the implementation of RFID technology and information standards to comply with food traceability requirements. The research is limited to fish supply chains; other sectors and supply chains need to be investigated for further generalisation of the results.Practical implications – Regulatory requirements on food traceability stipulate the implementation of food traceability systems, placing the responsibility on companies by authorities. The research presented can support managers in understanding the potential effects of implementing such systems.Originality/value – The discussion about logistics and food traceability has in part revolved around implementation of RFID technology and standardised approaches for handling information to preserve food quality and safety. This paper presents potential effects on logistic operations when implementing the EPCIS standard and RFID technology as a way of enabling traceability throughout food supply chains.